Intelligent traffic lights - Tun, Zuraidah (2005)
The Traffic Control system installed at an intersection regulates the behavior of road users to go through the intersection in a sequentially, systematic manner .Hence, increased safety for the road users at the expense of waiting period enabling all traffic to pass through the junction with minimum mishappenings The waiting period can sometimes not only be delaying factor, but also results an reduced traffic throughput at the intersection . Hence, resulting in unnecessary traffic build up. This project proposed an application of programmable logic controller (PLC) to controlling automated manufacturing process, that uses as programmable memory for internal storage of instructions that implement specific functions such as logic, sequence, timing, counting and arithmetic to control machines and processes.